Aktivitas antioksidan dan kandungan flavonoid total ekstrak etanol batang bajakah kalalawit (Uncaria cordata (Lour) Merr.) asal Kecamatan Loksado Kalimantan Selatan - Wathan, Nashrul; Safarina, Nor Rezky; Fitriana, Mia (Sasambo Journal of Pharmacy, 2024)
Bajakah kalalawit (Uncaria cordata (Lour) Merr.) is widely used by Dayak Tribes, based on empirical evidence, and often used to treat diabetes and various diseases such as cancer. This research aimed to determine the total flavonoid content and antioxidant activity of the ethanolic extract of U. cordata stems. The sample used bajakah kalalawit from Loklahung village, Loksado District, South Hulu Sungai Regency, South Kalimantan Province. Flavonoid levels were determined using quercetin standards, 10% AlCl3 reagent, and 5% acetic acid, then measured at a wavelength of 416 nm, while the antioxidant activity using DPPH 0.4 mM in UV-Vis spectroscopy at a wavelength of 516 nm. The results obtained were a thick extract mass with a dark brown color and a distinctive aroma. The total flavonoid content of the ethanol extract of U. cordata stems was found to be 3.6 Â± 0.086 % w/w equivalent quercetin and showed very strong antioxidant activity with an IC50 value of 9.159 ppm.